Aerogels for thermal insulation in high-performance textiles. Issue 2 (2nd April 2016) - Venkataraman, M.; Mishra, R.; Kotresh, T. M.; Militky, J.; Jamshaid, H.
ABSTRACT: For many garment applications where protection is needed against hostile environments, part of the requirement is for insulation to shield the wearer from extremes of temperature. For an insulating garment to be fully effective, it needs to allow the wearer to move freely so that they can carry out their intended activity efficiently. Traditional materials achieve their insulation by trapping air within the structure thereby not only limiting heat loss by convection but also making good use of the low thermal conductivity of air to cocoon the wearer within a comfortable environment. To achieve effective protection with conventional textiles, it is usually necessary to have a thick fibrous layer, or series of layers, to trap a sufficient quantity of air to provide the required level of insulation. Several disadvantages arise as a result. For example, thick layers of insulating textile materials reduce the ability of the wearer to move in a normal manner so that the conduct of detailed manual tasks can become very difficult; the layers lose their insulating capacity when the trapped air is lost as they are compressed; the insulating capacity falls rapidly as moisture collects within the fibrous insulator – it does not have to become sensibly wet for this to happen; just 15% moisture regain can give a dramatic reduction in insulating capacity. Not surprisingly therefore, there has been continued interest in developing insulators that might be able to overcome the disadvantages of conventional textile materials and improve the mobility of the wearer by allowing the use of only a very thin layer of extremely-high insulating performance to provide the required thermal protection. One class of materials from which suitable candidates might be drawn is aerogels; their attractiveness derives from the fact that they show the highest thermal insulation capacity of any materials developed so far. Despite sporadic high levels of interest, commercialisation has been slow. Aerogels have been found to possess their own set of disadvantages such as fragility; rigidity; dust formation during working and cumbersome, expensive, batch-wise manufacturing processes. They may well have been destined to become a product of minor interest, confined to very specialist applications where cost was of little concern. However, methods have been developed to combine aerogels and fibres in composite structures which maintain extremely high insulating capacity whilst demonstrating sufficient flexibility for use in garments. Ways have been found to prevent the formation of powder as aerogel composite fabrics are worked. Most significant though, is the achievement, arising from a project supported by the Korean Government, of a simplified one-step production process developed with the express aim of providing a substantial reduction in the cost of aerogels. Suitably-priced aerogel is now available and this should provide fresh stimulus for research and development teams to engage in new product development work utilising aerogels in textiles and garments for thermal insulation. The mechanisms through which aerogels achieve their outstanding thermal insulating ability is unconventional, at least in terms of materials used in textiles. This issue of Textile Progress therefore includes detail about thermal transport in aerogels before reviewing the various forms in which aerogels can now be made, some of their applications and the research priorities that are now beginning to emerge.